2022
DOI: 10.3389/fphys.2022.784705
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise in the Context of Air Pollution: An Emerging Research Topic

Abstract: Physical exercise (PE) brings physiological benefits to human health; paradoxically, exposure to air pollution (AP) is harmful. Hence, the combined effects of AP and PE are interesting issues worth exploring. The objective of this study is to review literature involved in AP-PE fields to perform a knowledge-map analysis and explore the collaborations, current hotspots, physiological applications, and future perspectives. Herein, cluster, co-citation, and co-occurrence analysis were applied using CiteSpace and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 189 publications
(183 reference statements)
0
19
0
Order By: Relevance
“…The references in the co-cited network ( Figure 4A ) were divided into 15 different clusters by cluster analysis shown in the timeline view ( Figure 5A ). These clusters were labeled by extricating terms from the titles of cited publications using the log-likelihood ratio algorithm due to its better performance in covering the “uniqueness and coverage” of all labels ( 11 , 18 ). As can be seen in Figure 5A , the cluster of prevalence comorbidities was the largest (#0), followed by controlled trial (#1) and acute gouty arthritis (#2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The references in the co-cited network ( Figure 4A ) were divided into 15 different clusters by cluster analysis shown in the timeline view ( Figure 5A ). These clusters were labeled by extricating terms from the titles of cited publications using the log-likelihood ratio algorithm due to its better performance in covering the “uniqueness and coverage” of all labels ( 11 , 18 ). As can be seen in Figure 5A , the cluster of prevalence comorbidities was the largest (#0), followed by controlled trial (#1) and acute gouty arthritis (#2).…”
Section: Resultsmentioning
confidence: 99%
“…WoS Core Collection (WoSCC) database is a typical citation database containing literature abstracts and other relevant data such as citation and research collaboration information, facilitating bibliometric analysis ( 19 ). Moreover, it could directly provide reference files that met the specific format requirements as dictated by bibliometric software ( 11 , 15 ). In our study, all literature was retrieved and downloaded from the Science Citation Index Expanded of WoSCC database on March 30, 2022, to avoid bias caused by database updates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology for calculating key indicators for analysis and identification of the most significant studies is described in detail in the works of van Eck and Waltman [27,28]. The validity of this approach is confirmed by studies of human physical activity [29][30][31][32].…”
Section: Methodsmentioning
confidence: 99%
“…The pre-retrieval results found that there was no publication before 1 January 1995; hence, the search time frame in this study was set from 1 January 1995 solstice to 31 December 2021. According to previous literature (21)(22)(23), "articles or reviews" were used as inclusion criteria, and the language was limited to "English." Related data were extracted and downloaded within 1 day to avoid bias due to frequent database updates.…”
Section: Data Source and Search Strategymentioning
confidence: 99%